Optimalisasi Peletakan Access Point Pada Jaringan WI-FI Menggunakan Metode Simulated Annealing Di Fakultas Teknik Universitas Riau - Hakim Ata Attaturk; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Placement of an access point using a Wi-Fi network is necessary to get the desired signal strength, especially from the receiver side. Access Point or transmitter as the signal sender is very important because the signal strength value is a parameter used to determine the coverage area (signal range) of the access point (transmitter). This research discusses the placement of access points in the Faculty of Engineering, University of Riau. In this case, 10 samples of Received Signal Strength Indication (RSSI) in dBm are processed to get the placement optimalization using Simulated Annealing Method with INSSIDER 4 Application. Propagation Line of Sight (LOS) is used to get distance between transmitter and receiver in meters. Signal strength does not only depend on the transmitter and receiver but also from the number of interference the research, it causes the decrease in the signal received by the receiver. Obtained coverage area after optimization 65.233% in the Faculty of Engineering, University of Riau. From the result, hoped this research can be used well to optimize access point placement on Wi-Fi networks using Simulated Annealing Method in the Faculty of Engineering, University of Riau. This system is implemented using Matlab Software.Keywords : Wi-Fi, Coverage Area, RSSI, Propagasi, LOS, Simulated Annealing, Matlab